Analisis Keamanan Sistem Informasi Akademik (SIAKAD) Universitas XYZ Menggunakan Metode Vulnerability Assessment - Erick Irawadi Alwi; Lutfi Budi Ilmawan (Faculty of Computer Science, University of Jember, 2021)
The use of academic information systems (siakad) has become mandatory for universities in providing user convenience in online academic administrative activities. However, sometimes college siakad has security holes that irresponsible people can take advantage of by hacking. This study aims to identify security vulnerabilities at XYZ Siakad University. The method used in this study is a vulnerability assessment method. A university syakad will conduct an initial vulnerability assessment by doing footprinting to get information related to XYZ syakad after that a vulnerability scan is carried out using vulnerability assessment tools to identify vulnerabilities and the level of risk found. Based on the vulnerability of the XYZ university's vulnerabilities, it is quite good, with a high risk level of 1, a medium risk level of 6 and a low risk level of 14. Researchers provide recommendations for improvements related to the findings of security holes in XYZ university Siakad from XSS (Cross Site Scripting) attacks, Clickjacking, Brute Force, Cross-site Request Forgery (CSRF) and Sniffing.